‘Rei Zulu', a Brazilian vale tudo showman (Revista de Artes Marciales Asiáticas, 2023)
In an itinerant caravan during the 1980s and 1990s, Rei Zulu challenged hundreds of fighters all over Brazil without choosing opponents, weight category, or specific modality for vale tudo fights, being considered by some journalists as the greatest showman of this competitive practice. This article aims to analyze the background and the path taken by Rei Zulu to become one of the most prominent vale tudo fighters in Brazil. Based on the triangulation of sources, including news from Brazilian newspapers, interviews, biographies, and books on the topic, we verified the existence of a previous historical context of this fighting style in Maranhão, his home state, and the modus operandi he developed for his shows. It was concluded that vale tudo was practiced in Maranhão, since the 1950's, and that the historical context played a significant role in the rise of Rei Zulu as a local icon. He was responsible for finding opponents through challenges on radios, newspapers, and television shows. Rei Zulu also took over the organization of the events, their promotion and ticket sales. He also performed the main fight of the show and entertained the audience with faces, dances, and acrobatics during the fight.